Fluoride Retention in Proximal Plaque and Saliva Using Two NaF Dentifrices Containing 5,000 and 1,450 ppm F with and without Water Rinsing - Nordström, A.; Birkhed, D. (Caries research, 2009)
A total of 26 healthy volunteers participated in this randomized 4-leg crossover study designed to measure fluoride (F) retention in interdental plaque and saliva. Two NaF dentifrices (5,000 and 1,450 ppm F) were used, with and without postbrushing water rinsing. The 4 tooth brushing methods were carried out twice a day during 2 weeks. Interdental plaque was collected from all proximal sites after each method, using dental floss. Immediately after the plaque sampling, the subjects were asked to brush their teeth with the same toothpaste and use the postbrushing water rinsing procedure as previously. Proximal saliva was collected from 4 interdental sites, using small paper points, before and up to 60 min after the brushing. The present study showed that the 5,000 ppm F toothpaste without postbrushing water rinsing resulted in the highest F concentration in both plaque and saliva and the 1,450 ppm F toothpaste with water rinsing in the lowest. The difference in the area under the curve of saliva F concentration versus time between the 2 methods was 4.2 times (p < 0.001). The corresponding difference in F concentration per unit weight of plaque (n = 16) was 2.75 times (p < 0.05). Water rinsing immediately after tooth brushing with 5,000 ppm reduced the F concentration in saliva by 2.4 times (p < 0.001). The difference in F values in saliva between 5,000/rinsing and 1,450/no rinsing was minor and not significant. The increase of F in both proximal saliva and plaque, using a dentifrice with 5,000 ppm F without postbrushing water rinsing, may be of clinical importance.